Effects of exogenous salicylic acid on growth characteristics and biochemical content of wheat seeds under arsenic stress - Zengin, Fikriye (Triveni Enterprises, 2015)
The present study illustrates the phytotoxic effect of As on wheat seedlings and pre-application of salicylic acid in alleviating toxic effect of arsenic. Wheat seedlings treated with different concentrations (50-400 mu M) of arsenic decreased the germination rate (34.7% and 86.9%), root and coleptile length, fresh and dry weight of roots and coleoptile, chlorophyll (67%) and protein content (27.1%), while increased proline and MBA content. However, pretreatment with 1mM saliycilic acid partially alleviated the toxic effect of arsenic on germination parameters and significantly reduced the proline (181.2%) and MDA (80%) content thereby increasing chlorophyll and protein content in As stressed wheat plants (p<0.01 or p<0.05). The data suggests that saliycilic acid reduced the damaging effects generated by As and enhanced the tolerance of wheat plants to arsenic toxicity.
Keywords: Arsenic toxicity; Chlorophyll; Germination; Proline; Salicylic acid; Wheet